1994
DOI: 10.1126/science.8178173
|View full text |Cite
|
Sign up to set email alerts
|

Gene for Familial Psoriasis Susceptibility Mapped to the Distal End of Human Chromosome 17q

Abstract: A gene involved in psoriasis susceptibility was localized to the distal region of human chromosome 17q as a result of a genome-wide linkage analysis with polymorphic microsatellites and eight multiply affected psoriasis kindreds. In the family which showed the strongest evidence for linkage, the recombination fraction between a psoriasis susceptibility locus and D17S784 was 0.04 with a maximum two-point lod score of 5.33. There was also evidence for genetic heterogeneity and although none of the linked familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
252
2
7

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(270 citation statements)
references
References 32 publications
9
252
2
7
Order By: Relevance
“…Cia5a and Cia5d also colocalize with several loci, or their syntenic regions, implicated in the regulation of rodent models of autoimmunity and inflammation (35-37, 60 -62), or in the susceptibility to human autoimmune diseases (63)(64)(65)(66). These studies suggest that both Cia5a and Cia5d genes could be relevant not only to arthritis, but also to other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 82%
“…Cia5a and Cia5d also colocalize with several loci, or their syntenic regions, implicated in the regulation of rodent models of autoimmunity and inflammation (35-37, 60 -62), or in the susceptibility to human autoimmune diseases (63)(64)(65)(66). These studies suggest that both Cia5a and Cia5d genes could be relevant not only to arthritis, but also to other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 82%
“…21 However, some of these scans found no evidence for linkage to HLA. 15,16,20 We subsequently showed that the evidence for linkage to HLA is markedly increased when linkage disequilibrium information is taken into account. 11,12 Recently, PSORS1 has been fine-mapped to the vicinity of HLA-C by linkage disequilibrium mapping.…”
Section: Introductionmentioning
confidence: 99%
“…2 The genetic linkage analyses presented so far also indicate several possible non-HLA gene locations, all of which have not been confirmed. [2][3][4][5][6] Two of these studies using a few large pedigrees presented data suggesting a psoriasis susceptibility locus on 17q and 4q respectively. 3,4 Trembath et al 2 recently reported a genome scan of 66 affected sib pairs in which four potential psoriasis susceptibility loci were identified, on chromosome 2p, 6p (HLA region), 8q and 20p.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Two of these studies using a few large pedigrees presented data suggesting a psoriasis susceptibility locus on 17q and 4q respectively. 3,4 Trembath et al 2 recently reported a genome scan of 66 affected sib pairs in which four potential psoriasis susceptibility loci were identified, on chromosome 2p, 6p (HLA region), 8q and 20p. Nair et al 5 confirmed the locus in the HLA region and presented two additional novel loci on chromosome 16q and 20p using 182 sib pairs in a genome-wide scan.…”
Section: Introductionmentioning
confidence: 99%